Alcoholic Liver Disease: A Mouse Model Reveals Protection byLactobacillus fermentum. Issue 1 (January 2016) - Barone, Rosario; Rappa, Francesca; Macaluso, Filippo; Bavisotto, Celeste Caruso; Sangiorgi, Claudia; Di Paola, Gaia; Tomasello, Giovanni; Di Felice, Valentina; Marcianò, Vito; Farina, Felicia; Zummo, Giovanni; de Macario, Everly Conway; et al.
Abstract : OBJECTIVES: : Alcoholism is one of the most devastating diseases with high incidence, but knowledge of its pathology and treatment is still plagued with gaps mostly because of the inherent limitations of research with patients. We developed an animal model for studying liver histopathology, Hsp (heat‐shock protein)‐chaperones involvement, and response to treatment. METHODS: : The system was standardized using mice to which ethanol was orally administered alone or in combination with Lactobacillus fermentum following a precise schedule over time and applying, at predetermined intervals, a battery of techniques (histology, immunohistochemistry, western blotting, real‐time PCR, immunoprecipitation, 3‐nitrotyrosine labeling) to assess liver pathology (e.g., steatosis, fibrosis), and Hsp60 and iNOS (inducible form of nitric oxide synthase) gene expression and protein levels, and post‐translational modifications. RESULTS: : Typical ethanol‐induced liver pathology occurred and the effect of the probiotic could be reliably monitored. Steatosis score, iNOS levels, and nitrated proteins (e.g., Hsp60) decreased after probiotic intake. CONCLUSIONS: : We describe a mouse model useful for studying liver disease induced by chronic ethanol intake and for testing pertinent therapeutic agents, e.g., probiotics. We tested L. fermentum, which reduced considerably ethanol‐induced tissue damage and deleterious post‐translational modifications of the chaperone Hsp60. The model is available to test other agents and probiotics with therapeutic potential in alcoholic liver disease.